Mali - A Participatory Approach to Livestock Development - Metzel, Jeffrey; Menudier, N. (World Bank, Washington, DC, 2012)
The livestock sector in Mali accounts for 43 percent of cattle exports in the Sahel sub-region. However, while the sub-sector accounted for 28.6 percent of agriculture's contribution to Gross Domestic Product (GDP), investment in it amounted to only 10.7 percent of the total budget allocation to rural development. The African Financial Community (CFA) devaluation in January 1994 increased the competitiveness of red meat from Sahelian countries (including Mali) bound for coastal importing countries (Benin, Cote d'Ivoire, Ghana, Togo). However, well before the devaluation, a major policy shift on the part of the Malian government emphasized the decentralization of political power and investment decisions. As part of this initiative, the government requested the World Bank's support on initiating a participatory process of policy formulation for the red meat sub-sector.